2021
DOI: 10.1021/acsami.1c04056
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Thin Polymer Coating as a Selective Thermal Emitter for Passive Daytime Radiative Cooling

Abstract: Radiative cooling to subambient temperatures can be efficiently achieved through spectrally selective emission, which until now has only been realized by using complex nanoengineered structures. Here, a simple dip-coated planar polymer emitter derived from polysilazane, which exhibits strong selective emissivity in the atmospheric transparency window of 8–13 μm, is demonstrated. The 5 μm thin silicon oxycarbonitride coating has an emissivity of 0.86 in this spectral range because of alignment of the frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…Passive radiative cooling polymer coatings (PRCPCs) represent one of the most facile and efficient energy-saving strategies for controlling spacing temperature. They usually have heterogeneous micro/nanostructures that reflect solar light (wavelength range of 0.3–2.5 μm) but allow for thermal emission to the cold outer space through the atmospheric longwave infrared (LWIR) transparent window (wavelength: 8–13 μm) . Such heterogeneous structures can be created by introducing cavities or particles into the polymer matrices. ,, This idea has inspired the design of various PRCPCs with excellent cooling performance. When great attention is focused on improving the coating’s cooling performance, many other aspects should also be considered for practical applications of these coatings. One aspect is the combination of additional desirable functions.…”
Section: Introductionmentioning
confidence: 99%
“…Passive radiative cooling polymer coatings (PRCPCs) represent one of the most facile and efficient energy-saving strategies for controlling spacing temperature. They usually have heterogeneous micro/nanostructures that reflect solar light (wavelength range of 0.3–2.5 μm) but allow for thermal emission to the cold outer space through the atmospheric longwave infrared (LWIR) transparent window (wavelength: 8–13 μm) . Such heterogeneous structures can be created by introducing cavities or particles into the polymer matrices. ,, This idea has inspired the design of various PRCPCs with excellent cooling performance. When great attention is focused on improving the coating’s cooling performance, many other aspects should also be considered for practical applications of these coatings. One aspect is the combination of additional desirable functions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed that angles <60° have a dominant contribution to the emission of passive cooling materials. 4 , 27 , 28 Therefore, the convection shield made from XPS and LDPE has a cone-shaped inner part, with a zenith angle of 60° to reduce the thermal loss (conduction and convection) area while marginally blocking the pathway of thermal radiation from the sample. Conductive heat transport from each gas compartment to the next would eventually cool the air below the convection shield.…”
Section: Resultsmentioning
confidence: 99%
“…[413] Hence, this offers a promising pathway to control of IR emission region through molecular-level design with appropriate chemical bonding. [414][415][416] Wang et al found experimentally that commercial encapsulated c-Si SCs can be cooled down by 2 °C in real environment using a 600 µm-thick pyramid-textured polydimethylsiloxane (PDMS) emitter without convection covering. This is due to a broadband emissivity close to 1 in mid-infrared range and an average transmittance of >90% in the absorption spectrum from 0.3 to 1.1 µm.…”
Section: Passive Radiative Cooling Of Pvmentioning
confidence: 99%